Traveling exhibitions and the popularization of geosciences (Research, Society and Development, 2020)
The contents linked to geosciences are fundamental for the citizen to be able to make a correct analysis of the Earth system, its variables and limitations, thus allowing conscious decisions to be made to guarantee the sustainability of our planet. Currently, in basic education, geoscientific contents are present in various disciplines such as physics, chemistry, geography and biology. This paper aims to present the results of a multidisciplinary approach performed by an extension project through itinerant exhibitions of rocks, minerals, fossils and archaeological materials. The exhibitions were held at schools and events located in the metropolitan region of Cuiabá, State of Mato Grosso, Brazil. The actions were developed through the Education and Geosciences Extension Project, between the years 2016 and 2018, and directly reached about 5,487 people. Thus, the exhibitions contributed to the process of teaching and learning of students and helped in the process of popularization of science. The developed methodology can be replicated elsewhere or be used as a reference for building similar actions.